Vaccine-preventable diseases: Uncommon disease primer for the front-line provider. Issue 2 (13th April 2019) - Desai, Shalini; MacDonald, Noni
Abstract: This practice point provides quick information for front-line health care providers on vaccine-preventable diseases which, given the success of immunization programs in Canada, are now uncommon or rarely seen. These infections can still occur in children and youth from Canada and elsewhere, and their clinical identification has important public health implications. Knowledge of signs and symptoms, immunizing travellers and newcomers to Canada, awareness of outbreaks in-community and elsewhere, and early consultation with an expert in infectious diseases and public health authorities in suspected cases, are key preventive care measures.